Abordaje al delito de hurto vivienda (2020)
The article describes an appreciation of the importance of cooperative work carried out by institutions with judicial police functions, as well as the relationships around the approach and treatment of the crime of home theft. In addition, it specifies the contributions of each of the institutions and the ideal way of operating according to their function, because the Police Function corresponds to an administrative management of the exercise of specific powers assigned by the police power to the administrative police authorities. Finally, some security cooperation strategies are exposed to counteract this crime as a result of an investigation.